Urgensi Pemahaman Local Wisdom Masyarakat Dalam Proses Penyuluhan Keagamaan Di Kalangan Penyuluh Agama Islam - suhandi, suhandi (AL-ADYAN, 2020)
Dakwah management must be carried out in accordance with sociocultural conditions of the concerned society, which is bound to a constant  progress triggered by globalization and the advance of technology, in turn often causing a multi-dimensional crisis. On the basis of this argument, this research is aimed at exploring the ways in which a Muslim adviser (Penyuluh Agama Islam) could effectively play his counselling roles in society. By focusing on a Muslim society in Langkapura, Bandar Lampung, this paper proposes the significant use of local wisdom for every dakwah management. It argues that every religious counselling activity needs to based on a well-constructed synergy between religious teachings and local wisdom of the society in which the activity of dakwah is taking place. By doing this, this research is (expected to be) able to produce a religious counselling model with a local wisdom approach, that may be adapted in another similar context.